Etton Causewayed Enclosure Bone Diagenesis data - Brock, Fiona; Loy, Charlotte; Dyer, Chris (Cranfield University, 2023)
XRF and FTIR data collected by Charlotte Loy as part of her Forensic Archaeology & Anthropology MSc thesis entitled 'Investigating the Peculiar Diagenesis of the Etton Causewayed Enclosure Bones' (2016). These Neolithic animal bones show unusual patterns of iron and manganese mineralisation.
Keywords: 'diagenesis'; 'bone'; 'Etton Causewayed Enclosure'; 'Neolithic'